Pseudo-analytical model for calculation of flat circular inductors with rectangular cross-section. (August 2018) - Ferrer Penalver, Pedro Luis; Crespillo Torriente, Carmen Leticia; da Silva Braga, Edmundo; Robert Alves, Marco Antonio; Roesler, Paulo Henrique; Mologni, Juliano Fujioka
Abstract: This paper proposes a new pseudo-analytical model for calculating dc inductance of flat circular inductors with rectangular cross section. The method developed divides the inductor into a finite number of spirals corresponding with its number of turns. Thus, the total inductance is calculated from the self-inductance of each spiral and the mutual inductance between them. The results were compared with experimental measures carried out in published works. Through 3D simulations made by the Finite Element Method was analyzed how the variation of all geometric parameters of the inductor influences the accuracy of the proposed model. The calculations performed proved to be in excellent agreement with simulations and experimental measurements. Results with smaller errors were obtained when compared to some of classical expressions of inductance calculation in flat circular inductors. In addition calculated inductance is use within an inductor ac equivalent circuit model and compared with 3D simulations. Highlights: New pseudo-analytical model for calculation of flat circular inductors. Total inductance is calculated from self-inductance and mutual inductance. Is studied how changes in all geometric parameters affects the model accuracy. Finite element method was used to evaluate the inductance of circular flat coils. In all comparisons made with simulations the error was never greater than 3.3%.